1999
DOI: 10.1002/(sici)1521-4044(19990901)50:9<317::aid-apol317>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Modification of polysulfone membranes. 2. Plasma grafting and plasma polymerization of acrylic acid

Abstract: Polysulfone membranes were modified with acrylic acid using plasma initiated graft polymerization (both in solution and vapor phase) and plasma polymerization. Changes on the surface were monitored by contact angle measurements and FTIR‐ATR technique. Pore size and ultrafiltration properties were also evaluated. Grafting in solution gave as a result hydrophobic membranes with pore size diameter signficantly reduced. Such membranes lost their ultrafiltration properties. Grafting in vapor phase seems to give bru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 24 publications
1
54
0
1
Order By: Relevance
“…Gancarz et al [92] compared three different approaches to modify PS membranes with AA via plasma-initiated graft polymerization; (i) grafting in solution; the plasma-treated polymer membrane was exposed to air for 5 min and dipped into a deaerated aqueous solution of monomer; (ii) grafting in vapour phase; when Ar plasma treatment on polymers was completed, a monomer vapour was introduced into the chamber; (iii) plasma polymerization of monomer vapours in a plasma reactor. It was shown that modified PS membranes prepared in a vapour phase possessed the highest membrane flux.…”
Section: Plasma Induced Grafting On the Membrane Surfacementioning
confidence: 99%
“…Gancarz et al [92] compared three different approaches to modify PS membranes with AA via plasma-initiated graft polymerization; (i) grafting in solution; the plasma-treated polymer membrane was exposed to air for 5 min and dipped into a deaerated aqueous solution of monomer; (ii) grafting in vapour phase; when Ar plasma treatment on polymers was completed, a monomer vapour was introduced into the chamber; (iii) plasma polymerization of monomer vapours in a plasma reactor. It was shown that modified PS membranes prepared in a vapour phase possessed the highest membrane flux.…”
Section: Plasma Induced Grafting On the Membrane Surfacementioning
confidence: 99%
“…Membranes were prepared by (i) substitution with functionalized groups, (ii) by polymer graft modification or (iii) by surface modification of prefabricated membranes [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the past few years have seen many advances in the field of ion beam surface modification of polymeric materials [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…These treatments lead to the formation of radicals 5 that are the promoters of surface cross-linking, functionalization, and degradation 3 . Argon is the most common inert gas used in plasma technology 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation